Vsx1 Transiently Defines an Early Intermediate V2 Interneuron Precursor Compartment in the Mouse Developing Spinal Cord - Francius, Cédric; Hidalgo-Figueroa, María; Debrulle, Stéphanie; Pelosi, Barbara; Rucchin, Vincent; Ronellenfitch, Kara; Panayiotou, Elena; Makrides, Neoklis; Misra, Kamana; Harris, Audrey; Hassani, Hessameh; Schakman, Olivier; et al. (Frontiers in Molecular Neuroscience, 2016)
Spinal ventral interneurons regulate the activity of motor neurons, thereby controlling motor activities. Interneurons arise during embryonic development from distinct progenitor domains distributed orderly along the dorso-ventral axis of the neural tube. A single ventral progenitor population named p2 generates at least five V2 interneuron subsets. Whether the diversification of V2 precursors into multiple subsets occurs within the p2 progenitor domain or involves a later compartment of early-born V2 interneurons remains unsolved. Here, we provide evidence that the p2 domain produces an intermediate V2 precursor compartment characterized by the transient expression of the transcriptional repressor Vsx1. These cells display an original repertoire of cellular markers distinct from that of any V2 interneuron population. They have exited the cell cycle but have not initiated neuronal differentiation. They coexpress Vsx1 and Foxn4, suggesting that they can generate the known V2 interneuron populations as well as possible additional V2 subsets. Unlike V2 interneurons, the generation of Vsx1-positive precursors does not depend on the Notch signaling pathway but expression of Vsx1 in these cells requires Pax6. Hence, the p2 progenitor domain generates an intermediate V2 precursor compartment, characterized by the presence of the transcriptional repressor Vsx1, that contributes to V2 interneuron development.